Serum Zinc Level Correlation with urinary Arginase in Patients with Bladder Cancer in Babylon Governorate - Ahmed F.F. Al-Baaj (Journal of Global Pharma Technology, 2018)
The present study aims to determine the level of serum zinc and its correlation with urinary arginase level in patients with bladder cancer compared to healthy control group. The type of present study is a case-control study. Forty-five patients with bladder cancer and forty-five healthy persons as a control in Babylon province /Iraq participated in this study. Results of the present study were shown significant decreases in serum zinc and significant increases in the urinary arginase levels in patients with bladder cancer when compared with control group, especially in muscle-invasive bladder cancer. Also, there was significance negative correlations of serum zinc level and urinary arginase level, In conclusions, present study propose that patients with bladder cancer in Babylon province have low zinc level comparing to normal subjects and this level decrease extremely as the cancer progress to higher stage. As regard zinc have antioxidant and immune boosting properties, zinc is a cofactors for a wide range of enzymes, zinc deficiency leads to decrease superoxide dismutase activity and that may be an important cause for initiating oxidative stress and worsen the prognosis of bladder cancer. The present study also proposesthat Increased level of urinary arginase in bladder cancer patients is related to increased production of polyamine and this will promote cancer growth and development to a higher stage. Keywords: Bladder cancer, Zinc, Urinary arginase.